1999
DOI: 10.1016/s0960-9822(99)80215-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal overexpression of APPL, the Drosophila homologue of the amyloid precursor protein (APP), disrupts axonal transport

Abstract: The two pathological hallmarks of Alzheimer's disease, amyloid plaques and neurofibrillary tangles, involve two apparently unrelated proteins, the amyloid precursor protein (APP) and Tau. Although it is known that aberrant processing of APP is associated with Alzheimer's disease, the definitive role of APP in neurons is not yet clear. Tau regulates microtubule stabilization and assembly in axons and is, thus, an essential component of the microtubule-associated organelle transport machinery. Although several g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
166
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(176 citation statements)
references
References 28 publications
7
166
0
1
Order By: Relevance
“…The effect of APP on ⌬Tau-induced cell death is not known, though recent reports show a physical interaction between Tau and APP, as well as their coupled axonal transport (Islam and Levy, 1997;Torroja et al, 1999). Levels of both APP and Tau mRNA are elevated in Down's syndrome (Oyama et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of APP on ⌬Tau-induced cell death is not known, though recent reports show a physical interaction between Tau and APP, as well as their coupled axonal transport (Islam and Levy, 1997;Torroja et al, 1999). Levels of both APP and Tau mRNA are elevated in Down's syndrome (Oyama et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted transport has been shown in AD (Cash et al, 2003;Praprotnik et al, 1996;Richard et al, 1989;Terry, 1996) and also amyotrophic lateral sclerosis (Williamson and Cleveland, 1999), however relatively few studies have examined this aspect of the disease (Kasa et al, 2000). Nonetheless, numerous factors implicated in AD including oxidative stress (de la Monte et al, 2000;Perry and Smith, 1997;Smith et al, 1995), APO e (Tesseur et al, 2000), and APP-L (Torroja et al, 1999) have all been shown to affect axonal transport. The observation that AbPP can serve as a kinesin cargo receptor (Kamal et al, 2000(Kamal et al, , 2001 as well as the inhibition of kinesin-dependent transport by tau overexpression (Ebneth et al, 1998;Stamer et al, 2002) should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, loss-and gain-of-function studies have revealed a role for APPL in synapse differentiation and axonal transport. [22][23][24] The mutant loechrig presents with a neurodegenerative phenotype that is strongly enhanced by Appl d mutants. 25 Overexpression of wild-type and mutant APPL proteins has also been shown to cause abnormal neurite outgrowth.…”
mentioning
confidence: 99%